Cardiac function monitoring during marathon training based on smart medical wearable sensor device - Cai, Hongjuan; Cai, Miao (Molecular & Cellular Biomechanics, 2024)
In recent years, intelligent wearable sensor devices have developed rapidly and can be seen everywhere in daily life. With the rapid development of electronic components and the continuous improvement of their performance, intelligent wearable intelligent products have gradually become possible and have shown explosive growth. In addition, intelligent wearable electronic devices have many advantages that traditional devices do not have. With the popularity of fitness wearable devices, intelligent wearable devices can also be used for real-time heart rate and dynamic electrocardiogram (ECG) monitoring during marathon sports. It can effectively prevent sudden death. During marathon training and other health services, it is very important to use intelligent wearable sensor devices to monitor heart function. This paper puts forward a heart function monitoring system for marathon training based on intelligent wearable sensor, expounds the origin of marathon sports and the importance of heart function monitoring for marathon athletes during training. This paper discusses the technology and construction method of heart rate monitoring system based on intelligent wearable sensor device. At the same time, relevant experiments are carried out to verify the relevant performance of the intelligent wearable sensor device in the algorithm. The results show that the R wave detection accuracy of wearable devices based on traditional algorithms is usually between 92% and 93%. The R wave detection accuracy of the intelligent wearable sensor device improved by the algorithm in this paper has been improved to more than 97%, and the R wave detection accuracy of the algorithm in this paper is much higher than that of the traditional algorithm. This also reflects the effectiveness of the intelligent wearable sensor device of the algorithm during the training of marathon athletes.